Analisis kekuatan dan safe working load (SWL) pada single crane hook menggunakan SolidWorks - Bhakti, Zikri Amal; Subekti (KOLECER Scientific Journal of Mechanical Engineering, 2025)
The use of crane hooks in lifting operations requires special attention to structural strength and safety factors to prevent potentially fatal failures. This study aims to analyze the strength and determine the Safe Working Load (SWL) of a single crane hook with three cross-sectional variations: trapezoidal, circular, and rectangular. The Finite Element Method (FEM) was applied using SolidWorks 2018, and the results were validated through manual calculations. The material used was DIN 34CrNiMo6 alloy steel with a uniformly applied 5 Ton or 49.050 N load. The trapezoidal section showed the best performance with a maximum stress of 720.44 MPa, deformation of 1.47 mm, safety factor of 1.34, and SWL of 13,573.61 N (1,383.65 kg). The rectangular section produced a maximum stress of 793.64 MPa, deformation of 1.63 mm, safety factor of 1.21, and SWL of 11,965.24 N (1,219.70 kg). Meanwhile, the circular section showed the lowest performance with 1,072.27 MPa of stress, 1.88 mm deformation, safety factor of 0.89, and SWL of 8,701.47 N (887.00 kg). Therefore, the trapezoidal section is recommended as the safest and most optimal design for lifting applications.